Determination of Information Technology, Recruitment and Training towards Talent Management - Wenny Desty Febrian; Muhamad Al Faruq Abdullah; Bias Yulisa Geni (Dinasti International Journal of Education Management And Social Science, 2024)
Literature review research on the determinants of information technology, recruitment and training on talent management is a scientific literature article in the scope of human resource management science. The purpose of this HR management literature research is expected to build a hypothesis of the influence between variables which can later be used for further research. The approach or method used in this literature review research is descriptive qualitative. The data collection technique used is literature study or analyzing relevant previous research. The data used in this descriptive qualitative research was obtained from previous research that is relevant to this research and sourced from academic media such as articles published in the Scopus Elsevier Journal, Emerald, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and e-books. The results of this literature review are: 1) Information Technology influences Talent Management; 2) Recruitment influences Talent Management; and 3) Training influences Talent Management.